Pengaruh Persepsi Risiko, Viral Marketing, dan Metode Pembayaran terhadap Keputusan Pembelian - Sari, Revie Novita (Universitas Darwan Ali, 2024)
The rise of online shopping has raised concerns among various parties, especially regarding security issues. The risks involved are significant, ranging from product mismatches to fraud. Despite the convenience of payment methods and extensive promotions, perceived risk remains an important factor. Shopee, as an e-commerce platform with the highest number of purchases and visits, is also not exempt from these concerns. To address this issue, the Cash on Delivery (COD) payment method was introduced, allowing customers to pay only after receiving their orders. This study aims to examine the influence of perceived risk, viral marketing, and payment methods on purchasing decisions among Shopee users, specifically those using the COD payment method. The population of this study consists of all residents in Hampalit village who have made purchases using the Shopee app. A total of 102 respondents were selected using purposive sampling. Data was collected through a questionnaire, and multiple regression analysis was used to analyze the data. The results of this study indicate that: Perceived risk has no significant effect on purchasing decisions, viral marketing has a positive and significant effect on purchasing decisions, and payment methods have a positive and significant effect on purchasing decisions.